Activité antimicrobienne des souches de lactobacillus sp associées aux antibiotiques vis-à-vis de certains pathogènes - Kaddour, Souhila; Azzi, Ilhem (My University, 2020)
This work aims to study the antibacterial activity of lactic acid bacteria strains associated with antibiotics against pathogenic bacteria. An analysis of the various research works on the use of antibiotics or alternative substances associated with antibiotic therapy is done to evaluate the synergistic effects importance and to discuss the results obtained by different authors. The evaluation of synergistic positive or antagonistic effect of the antimicrobial agents combinations (antibiotic + bacteriocin; essential oil + antibiotic; essential oil + bacteriocin) is done by the E-test method or checkerboard used for the in vitro comparison of the efficacy of different antimicrobial combinations against several pathogenic strains. Analysis of selected articles confirm the possibility to have an antibacterial activity with different combinations of bacteriocins and antibiotics such as polymyxin and colistin by the synergistic effect against pathogenic strains such as (Escherichia coli; Listeria monocytogenes; Salmonella choleraesuis; Pseudomonas aeruginosa; Yersinia enterocolitica) by the method of well diffusion on agar. Additionally, it is possible to have antibacterial activity by different essential oils such as Pelargonium asperum oil associated to bacteriocins or antibiotics for different pathogens inhibition (Staphylococcus aureus; and Escherichia coli).
Keywords: lactic acid bacteria; antibiotic; antibacterial activity; pathogens; synergistic effect